2016
DOI: 10.1002/acp.3220
|View full text |Cite
|
Sign up to set email alerts
|

Creating Memories for False Autobiographical Events in Childhood: A Systematic Review

Abstract: SummaryUsing a framework that distinguishes autobiographical belief, recollective experience, and confidence in memory, we review three major paradigms used to suggest false childhood events to adults: imagination inflation, false feedback and memory implantation. Imagination inflation and false feedback studies increase the belief that a suggested event occurred by a small amount such that events are still thought unlikely to have happened. In memory implantation studies, some recollective experience for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
76
0
11

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(88 citation statements)
references
References 92 publications
1
76
0
11
Order By: Relevance
“…Research has shown that it is also possible, under certain circumstances, to develop false memories for entire events (e.g., Loftus and Pickrell, 1995), including criminal events (Shaw & Porter, 2015; but see also Wade, Garry, & Pezdeck, 2018;Shaw, 2018). Systematic reviews of false memory research have seen rates ranging from 15% (Brewin & Andrews, 2017; but see Otgaar, Merckelbach, Jelicic, & Smeets, 2017;Nash, Wade, Garry, Loftus, & Ost, 2017) to 30% (Scoboria et al, 2017) of participants developing false memories.…”
Section: Recovered Memory Therapy and Beliefs About Repressed Memorymentioning
confidence: 99%
“…Research has shown that it is also possible, under certain circumstances, to develop false memories for entire events (e.g., Loftus and Pickrell, 1995), including criminal events (Shaw & Porter, 2015; but see also Wade, Garry, & Pezdeck, 2018;Shaw, 2018). Systematic reviews of false memory research have seen rates ranging from 15% (Brewin & Andrews, 2017; but see Otgaar, Merckelbach, Jelicic, & Smeets, 2017;Nash, Wade, Garry, Loftus, & Ost, 2017) to 30% (Scoboria et al, 2017) of participants developing false memories.…”
Section: Recovered Memory Therapy and Beliefs About Repressed Memorymentioning
confidence: 99%
“… We find Brewin’s (2016) critiques of the narratives, power, and coherence measures in Rubin et al, (2015) without merit; his suggestions for a “revised formulation” of coherence are contradicted by data readily available in the target article, but ignored. We place Brewin’s commentary in a historical context and shows that it reiterates views of trauma memory fragmentation that are unsupported by data.…”
mentioning
confidence: 55%
“…Memory researchers have studied how autobiographical false memories could be implanted through suggestive interviewing techniques (Loftus & Pickrell, 1995;Scoboria et al, 2017). However, scholars have criticized these studies on the notion that victims of such false memory cases often recall repeated episodes of child sexual abuse, rather than a single one (Brewin & Andrews, 2017;Blizard & Shaw, 2019). An important feature in these cases of false memory for child sexual abuse is that the alleged adult victims often reported to have been repeatedly sexually abused.…”
Section: Implanting False Autobiographical Memories For Repeated Eventsmentioning
confidence: 99%